2008
DOI: 10.1007/s11908-008-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of supraglottitis (Epiglottitis)

Abstract: Acute supraglottitis is a serious, potentially fatal infection in both adults and children. Haemophilus influenzae type b (Hib) is the most common cause in children, even in this era of the Hib vaccine. Most cases of acute supraglottitis in adults are thought to be caused by other bacterial organisms, viral or combined viral-bacterial infections, and noninfectious etiologies. Early visualization of the larynx is essential, as is establishment of a secure airway in selected cases. Most cases will respond to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 32 publications
0
65
0
1
Order By: Relevance
“…1 A more recent study estimates the current annual incidence of pediatric epiglottitis to be between 0.6 and 0.78 cases per 100,000 persons immunized. 2 Furthermore, since the introduction of the vaccine, the mean age of presentation in the pediatric population has increased, from 5.8 years in 1992 to 1997 to 11.6 years in 1998 to 2002. 3 Finally, it has shifted the pathogenesis of the disease, with the most common causative organisms now being Streptococcus pneumonia and other Streptococcus species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A more recent study estimates the current annual incidence of pediatric epiglottitis to be between 0.6 and 0.78 cases per 100,000 persons immunized. 2 Furthermore, since the introduction of the vaccine, the mean age of presentation in the pediatric population has increased, from 5.8 years in 1992 to 1997 to 11.6 years in 1998 to 2002. 3 Finally, it has shifted the pathogenesis of the disease, with the most common causative organisms now being Streptococcus pneumonia and other Streptococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…2 Signs of severe upper airway obstruction necessitate intervention, but a report on epiglottitis concluded that signs, such as RR, lateral airway radiographs, and arterial blood gas measurements "are of much less value than the child's general appearance to an experienced observer." 19 This emphasis on physical examination skills and heightened suspicion is critically important to a generation of physicians who have likely never seen a case of acute epiglottitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although bacterial infections have been implicated in this condition, 7 other causes include trauma, 8 viruses, 9 chemicals, 10 recreational drugs 11 and chemotherapy. 7 Some authors state that there are no reproducible clinical signs indicating potential airway compromise, whilst others suggest that a rapid clinical course (especially within the first 24 hours of the illness) is more predictive of a requirement for airway intervention, which includes tracheostomy and endotracheal intubation. 3,13 Due to the anatomical location of the inflammation, meticulous assessment and regular monitoring for deterioration is paramount, in order to prevent sudden respiratory catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the establishment of an artificial airway, the physiologic function of the ventilated patient's epiglottis may be weakened or even lost. However, the high pressure of the airway, which is utilized for cough, cannot be generated, which seriously blocks cough [4][5][6]. Furthermore, an artificial airway may accelerate the secretion of the lung, and restrain cilium movements [7,8].…”
Section: Introductionmentioning
confidence: 99%